Principles of economics in a nutshell - Garbo, Lorenzo; Isenberg, Dorene, 1949-; Reksten, Nicholas (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Principles of Economics in a Nutshell provides a succinct overview of contemporary economic theory. This key text introduces economics as a social science, presenting the discipline as an evolving field shaped within an historical context rather than a fixed set of ideas. Chapters on microeconomics introduce concepts of scarcity and tradeoffs, market analysis (the Marshallian cross of supply and demand) and the theory of the firm and market structure. Chapters on macroeconomics begin with an explanation of national income accounting, followed by discussions of macroeconomic theory in the goods market and in the money market from both a Keynesian and Classical view. The text concludes with examples of how to expand upon core material; using the examples of wage discrimination and climate change, it examines these issues from the perspectives of feminist and ecological economics. This book will be of great importance to students new to economics and is ideal for use on single-semester Principles courses or as a primer on economics courses in other settings. The text is fully supported by online resources, which include a set of analytical questions and suggestions for further reading for each chapter"--
OCLC-licensed vendor bibliographic record.
Keywords: Economics; BUSINESS & ECONOMICS / Economics / Macroeconomics; BUSINESS & ECONOMICS / Economics / Microeconomics; BUSINESS & ECONOMICS / Economics / General